Guided Inquiry-Based Basic Chemistry Practicum Guidelines and Its Impact on Students' Science Process Skills and Critical Thinking Skills - Ayu Rahayu; Rina Sardiana Sari (Jurnal Pendidikan Kimia Indonesia, 2023)
Science process and critical thinking skills must be possessed by students as prospective professional teachers. Quality practicum activities with quality teaching materials can improve science process skills and low critical thinking. The practicum guide only asks students to carry out practical activities according to existing procedures, so students cannot build their skills. This study aims to develop an inquiry-based practicum guide that meets the valid, practical, and effective criteria for science process skills and critical thinking. This research is development research based on the Hannafin & Peck model with three stages, namely needs assessment, design, development, and implementation, piloted on a small scale, namely 20 students in basic chemistry courses. The results showed (1) Valid with a value of 3.5. Practical with a score of 3.81 on lecturer activities and 3.3 on student activities. Effective with 90.5% getting a positive response. (2) Science process skills are very good, with a score of 88.54%, and critical thinking skills with the results of hypothesis testing Sig (0.001) > 0.05, while the gain score test is 0.45 in the medium category. This guided inquiry-based practicum guide can be used because students design, formulate hypotheses, and conclude independently to improve their science process and critical thinking skills.